Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Halal Fashion - Tsania, Zukhrufa Hizballah; Muiz, Aris Nurul (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2025)
Halal fashion is one of the halal sectors that is currently very promising. Considering that the majority of modern Indonesian Muslims prefer to wear clothes that cover their private parts. Apart from being a representation of modern trends, the term "halal" in fashion also refers to certain beliefs. The aim of this research is to analyze and determine the factors that influence halal fashion purchasing decisions using case studies on students in Tasikmalaya. This type of research is quantitative descriptive research with a sample of 138 students in Tasikmalaya with the classification of students who are currently studying at universities/campuses in the Tasikmalaya area and have purchased halal fashion clothing such as syar'i clothing or Muslim clothing, etc. In the future, samples can be added covering all of Indonesia or between countries. The data analysis technique used in this research is the Structural Equation Model Partial Least Square (SEM-PLS). Based on the results of hypothesis testing, it shows that all hypotheses are accepted, namely price, digital marketing and knowledge on halal have a significant influence on halal fashion purchasing decisions.